2015
DOI: 10.4236/oalib.1101489
|View full text |Cite
|
Sign up to set email alerts
|

Health Seeking Behaviours of Patients Attending Primary Eye Care Centre in Nigeria

Abstract: Purpose: To determine health seeking behaviour in relation to non-orthodox eye medication use among patients attending a primary eye health center in Nigeria. Materials and Methods: It was a cross-sectional study of consecutive respondents. Participants' socio-demographic profile, types and pattern of harmful traditional eye medications (HTEMs) use were obtained using a pre-tested questionnaire. Data analysis was by SPSS version 20.0. Results: Of the 303 patients enrolled in the study, 153 (50.5%) were males a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
2
0
1
Order By: Relevance
“…[9] - [14] The poor utilization of orthodox eye care services in this study agrees with most other studies in Nigeria and Africa [17] - [21] ; but conflicts with the study conducted at Afon, a rural community in Kwara state, where most respondents (62.5%) used orthodox eye care services. [9] It has been reported that utilization of existing eye care infrastructure in Nigerian communities is as low as 25% compared to the optimum target utilization set at 90%.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…[9] - [14] The poor utilization of orthodox eye care services in this study agrees with most other studies in Nigeria and Africa [17] - [21] ; but conflicts with the study conducted at Afon, a rural community in Kwara state, where most respondents (62.5%) used orthodox eye care services. [9] It has been reported that utilization of existing eye care infrastructure in Nigerian communities is as low as 25% compared to the optimum target utilization set at 90%.…”
Section: Discussionsupporting
confidence: 63%
“…[1], [14], [15], [16] Non-orthodox eye medications appear to be better patronized probably because they may be more readily available and cheaper. It has also been suggested that the rural dwellers have more trust and confidence in the traditional healers perhaps due to the presumed failure of modern medicine to cure certain eye diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In Ghana, people living in communities with poor or inaccessible eye care facilities were more likely to seek alternatives to orthodox eye care services including self-medication, traditional healers, itinerant couchers, and patent medicine vendors (PMVs), some of which may be harmful. [ 4 ] Poor eye health-seeking behaviour has been identified in some studies done in Nigeria,[ 5 6 7 8 9 ] including delays in seeking orthodox eye care or not seeking orthodox eye care at all.…”
Section: Introductionmentioning
confidence: 99%
“…Катаракта -заболевание, являющееся наиболее частой причиной нарушения зрения в пожилом возрасте и ведущей причиной слепоты [1][2][3]. По данным ВОЗ, удельный вес катаракты в структуре заболеваемости органов зрения составляет 47% [4].…”
unclassified